Public engagement in health technology assessment in Brazil: the case of the public consultation on National Clinical Guidelines for Care in Normal Birth - Viviane Karoline da Silva Carvalho; Everton Nunes da Silva; Jorge Otávio Maia Barreto (BMC Public Health, 2021)
Abstract Background There is a growing body of literature that recognizes the importance of public engagement in health technology assessment. However, there is still uncertainty regarding how the results should be recorded, analyzed, and used by decision makers. Objective Synthesize the contributions of the Brazilian public (women, health professionals, managers, educational institutions, and companies) about the implementation of the National Clinical Guidelines for Care in Normal Birth from the public consultation carried out in Brazil. Method IRaMuTeQ software was used to organize and summarize the corpus based on three types of analysis: descriptive statistics; descending hierarchical classification; and specificities analysis. The public consultation was conducted in 2016 by the National Committee for Health Technology Incorporation (CONITEC) in the Brazilian public health system as part of the guideline development process. Results The corpus consisted of 303 texts, separated into 1233 text segments, 1081 of which were used, corresponding to retention of 87.67%. Five classes emerged from our analyses: mandatory presence of an obstetrician during labor and delivery in hospital settings; barriers and facilitators for guideline implementation; use of evidence—based practices by health professionals; progression of labor and delivery and women’s rights; and mobilization to promote the guideline For each class, the most frequent words and sentences with the highest chi-squared scores were presented. Barriers were associated with lack of financial resources, training and professional motivation, and facilitators with training to change the practices of health professionals. Obstetric nurses emerged as an alternative for supervising normal births as well as the mandatory presence of an obstetrician during childbirth in hospital settings. Conclusion Our findings summarize the contributions provided by the Brazilian public and shed some light on the barriers and facilitators of clinical guidelines for care in normal birth. These topics are not typically explored by quantitative studies. Including this information in the decision-making process would not only increase public engagement, but provide greater evidence for implementing the clinical guidelines nationwide.